"Nutritional Literacy Gap": Investigating the Correlation Between Macronutrient Intake and Nutritional Status in First-Year Students (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
This quantitative study aimed to investigate the correlation between nutritional literacy, macronutrient intake encompassing energy, carbohydrates, proteins, and fats and the nutritional status of first-year undergraduate students in the Nutrition Study Program at the State University of Surabaya. First-year students represent a vulnerable demographic prone to nutritional challenges due to significant lifestyle transitions and irregular dietary patterns. In this context, nutritional literacy serves as a pivotal determinant influencing daily food selection and health outcomes. Employing a cross-sectional design, the research was conducted between September and October 2025, involving 83 respondents selected through simple random sampling. Data collection integrated anthropometric measurements for body weight and height, validated nutritional literacy questionnaires, and 2x24-hour food recalls to capture detailed dietary intake. Statistical analysis was performed using the Spearman’s rho correlation test to identify significant relationships between variables. The findings revealed that 57.8% of students possessed adequate nutritional literacy. However, alarming deficiencies were observed in dietary habits: 100% of respondents exhibited inadequate energy and carbohydrate intake, while the majority also showed insufficient protein (81.9%) and fat (78.3%) consumption. Despite these gaps, 51.8% of the students maintained a normal nutritional status. The analysis concluded that no significant correlation existed between nutritional status and nutritional literacy (p=0.869), energy intake (p=0.231), protein (p=0.781), or fat (p=0.771). Conversely, a significant correlation was identified between carbohydrate intake and nutritional status (p=0.040; r=-0.226). These results underscore that theoretical literacy does not inherently guarantee optimal dietary fulfillment. Consequently, there is an urgent need to enhance students' awareness and practical application of nutritional literacy in daily food selection. This study highlights the necessity for targeted educational interventions to bridge the gap between nutritional knowledge and actual dietary behavior among university students.